2016
DOI: 10.1007/s10453-016-9432-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the pollen season start in Corylus avellana and Alnus glutinosa

Abstract: Hazel (Corylus avellana L.) and black alder (Alnus glutinosa (L.) Gaertn.) are important sources of airborne pollen and represent an allergen threat during the flowering period. Researches on airborne pollen concentrations in both species are useful in allergology, as well as for fruit production for hazel. The aims of the present study were: (1) to investigate the relationships between environmental conditions and the airborne pollen concentration of hazel and black alder during the flowering period by correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Previous studies have noticed the importance of chilling accumulation for alder and other winterflowering trees in the last autumn. The chilling phase has been identified as the most important thermal accumulation period for alder in the Mediterranean climate while forcing requirements are satisfied in a short period of time in alder trees of Southern Europe (González-Parrado et al, 2006;Novara et al, 2016). It supports the results of our study, but such behavior with respect to the thermal requirements may be different in other climatic conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have noticed the importance of chilling accumulation for alder and other winterflowering trees in the last autumn. The chilling phase has been identified as the most important thermal accumulation period for alder in the Mediterranean climate while forcing requirements are satisfied in a short period of time in alder trees of Southern Europe (González-Parrado et al, 2006;Novara et al, 2016). It supports the results of our study, but such behavior with respect to the thermal requirements may be different in other climatic conditions.…”
Section: Discussionsupporting
confidence: 89%
“…autumn temperatures have become warmer during recent years. Similar phenological trends were found in other Mediterranean areas of Southern Europe, such as Italy and the Iberian Peninsula, where a slight trend towards later start-dates of alder pollen seasons has been documented (Jato et al, 2013;Novara et al, 2016;Rodríguez-Rajo et al, 2011). On the other hand, these results contrasted with those from Central and Northwestern Europe (United Kingdom, Austria, Finland, Norway, Sweden, Iceland) (Emberlin et al, 2006;Jäger et al, 1996;Lind et al, 2016;Smith et al, 2014), all of which reported negative trends, i.e., alder flowering earlier over time.…”
Section: Discussionsupporting
confidence: 81%
“…The release from winter dormancy is environmentally mediated by species-specific responses to temperature and photoperiod. The “chilling and heating” mechanism is similarly described for the flowering phase and pollen release, especially for alder and hazel in early year, and so has been used for the development of pollen forecast models (Novara et al 2016 ). However, our study does not take into account the chill accumulation during the previous winter period.…”
Section: Discussionmentioning
confidence: 99%
“…However, these consequences may significantly vary from one region to another, depending on the selected taxon and on the clime (Donders et al 2014 ; Emberlin et al 2002 ; Galán et al 2005 ). Indeed, the complexity of interactions and overlapping actions between meteorological parameters, the plant physiognomy and phenology, the land use, and other environmental factors presents a serious challenge for researchers to develop robust and precise pollen forecast models (Novara et al 2016 ; Sofiev et al 2015 ). Pollen monitoring thus plays a crucial role to improve these models by feeding them with historical data.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, hazel requires genetically compatible pollinizer cultivar, but pollination remains an uncertain process dependent on numerous factors, such as rainfall, humidity, wind, which can affect this phenomenon in different ways (Ellena et al, 2014;Novara et al, 2016) both during the catkins elongation and pollen dispersion. Moreover, male and female flowering of compatible cultivars should overlap in order to ensure a correct pollination, but flowering can vary from year to year and the response of male anď et al, 2012; Ellena et al, 2014).…”
Section: Introduction Abstractmentioning
confidence: 99%